While The Clock Ticked - Dixon Franklin W.; Franklin W. Dixon (Canada Franklin W. Dixon, 1932)
Frank and Joe Hardy investigating mysterious death threats received by banker Raymond Dalrymple inside a locked "sunset room" in his new home.
Keywords: The plot centers on Frank and Joe Hardy investigating threats against banker Raymond Dalrymple, whose newly purchased, historic home (the old Purdy estate) contains a secure, time-locked room where he has been receiving mysterious, threatening notes; revolves around the investigation of a mysterious, ticking mansion and a hidden, invaluable item. The primary moral lessons from the story